Ebb tide in blue: Recent sub-national elections in the Australian federation. Issue 3 (27th May 2018) - Bolwell, Dain; Eccleston, Richard
ABSTRACT: This article analyses the extent and nature of nationalization of state and territory elections in Australia, both in terms of how similar state and territory voting patterns are to federal results, as well as 'second-order' effects that indicate how much dissatisfaction with the existing federal government spills over into state and territory elections. We include assessments of campaign issues and impacts in order to see how far voters hold both federal and state and territory governments accountable. While we find both similarities in voting patterns between the two tiers and small second-order effects in the regions, we argue that swings were linked to national policy paralysis in the face of major issues that impacted differently across sub-national electorates. Coalition decline was exacerbated by leadership instability and increasing concern by its parliamentarians at their fading political popularity.